Indigenous parents and child welfare: Mistrust, epistemic injustice, and training - Leckey, Robert; Schmieder-Gropen, Raphael; Nnebe, Chukwubuikem; Clouthier, Miriam (Social & Legal Studies, 2022)
The settler state's taking of Indigenous children into care disrupts their communities and continues destructive, assimilationist policies. This article presents the perceptions of lawyers, social workers and judges of how Indigenous parents experience child welfare in Quebec. Our participants characterized those experiences negatively. Barriers of language and culture as well as mistrust impede meaningful participation. Parents experience epistemic injustice, wronged in their capacity as knowers. Mistrust also hampers efforts to include Indigenous workers in the system. Emphasizing state workers’ ignorance of Indigenous family practices and the harms of settler colonialism, participants called for greater training. But critical literature on professional education signals the limits of such training to change institutions. Our findings reinforce the jurisdictional calls away from improving the system towards empowering Indigenous peoples to run services of child welfare. The patterns detected and theoretical resources used are relevant to researchers of other institutions that interact with vulnerable populations.
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; australie; canada; care; cours; cycles supérieurs; discipline; droit; enfants autochtones; fem9000; injustice; inégalités; nouvelle-zélande; océanie; politique assimilationniste; périodes historiques; racisme; régions géographiques; santé; science politique et droit; sciences humaines; sciences sociales; système colonial; systèmes d'oppressions; thématiques; violences; états coloniaux

Mémoires de FAQ - Journée de débat général des droits des femmes et filles autochtones lors de la 79e session du CEDAW - 2021 - Femmes autochtones du Québec (2021)
Keywords: 2000 à aujourd'hui; 2020-2029; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminisme autochtone; pdf; pol4105; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; études autochtones

Sexualized Violence and Colonialism: Reflections on the Inquiry into Missing and Murdered Indigenous Women - Razack, Sherene (Canadian Journal of Women and the Law, 2016)
Introduction to the special isuue of the Canadian Journal of Women and the Law on the "Missing and Murdered Indigenous Women Conference".
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; féminicide; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; science politique et droit; sexisme; système colonial; systèmes d'oppressions; thématiques; violences

Infiltrated Intimacies: The Case of Palestinian Returnees - Shalhoub-Kevorkian, Nadera (Feminist Studies, 2016)
This essay examines Palestinian women’s struggles following the 1948 Nakba, when many challenged their uprooting by attempting to return back to their homes and land. Analyzing women’s narratives recounting their experiences from 1948 to 1953 within the context of the settler-colonial regime of control, the essay reveals Israel’s criminalization of the return of Palestinian refugees as acts of “infiltration,” and the unspoken gendered history of trauma that infiltrates the intimate space of women’s families, bodies, and lives. By sharing women’s voices and their embodied memories about childbirth, menstruation, intimate family life, their homes, and domestic life, the article works to provide gender analyses of the political work of suffering, to demonstrate how women were uniquely targeted and affected by such criminalization. Unmasking the political history of trauma and suffering and borrowing meanings from women cast out as illegal by the Israeli state, positions women returnees as frontliners against the political illegality and criminalization of settler colonialism.
Keywords: 1900-1999; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; asie; cours; discipline; droit; féminisme arabe; féminisme décolonial; féminisme islamique; histoire et politique; israël; nakba; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

“It Happened More Than Once”: Freezing Deaths in Saskatchewan - Razack, Sherene (Canadian Journal of Women and the Law, 2014)
Le présent article analyse les enquêtes et une commission sur des décès par hypothermie en Saskatchewan, au Canada. Il souligne les économies raciales et d’espace liées à ces décès, et il suggère que les relations structurelles propres au colonialisme de peuplement produisent et encouragent les expulsions continues et quotidiennes d’autochtones de la part des colonisateurs, expulsions qui sont inévitablement violentes. La ville coloniale appartient au colonisateur et son occupation est inévitablement récusée par la présence des autochtones dans la ville. L’autochtonité met mal à l’aise, car elle conteste la prétention du colonisateur à la légitimité en remettant en cause une fiction très tenace dans les états coloniaux selon laquelle les peuples autochtones seraient à l’agonie. La pratique qui consiste à repousser les autochtones aux périphéries de la ville vient du besoin des colonisateurs de maintenir les lignes de force des villes coloniales. Aujourd’hui, quand cette pratique est scrutée par le droit, comme ce fut le cas dans l’enquête sur le décès de Neil Stonechild, et dans des enquêtes sur les décès par hypothermie, elle est considérée soit comme le fait de quelques policiers sans vergogne ou encore on la nie carrément. Ce qui demeure dans les registres judiciaires, toutefois, ce sont les économies raciales d’espace dans la ville coloniale et la dévalorisation persistante de la vie autochtone, une dévalorisation que la loi produit et soutient. Dans la première partie, je présente des idées sur les économies raciales et d’espace de la ville coloniale. Dans la deuxième partie, j’étudie le cas du décès de Neil Stonechild, ainsi que la réponse du droit à ce décès, la Commission d’enquête Wright. Dans la troisième partie, j’analyse les enquêtes sur les décès par hypothermie de Rodney Niastus et de Lawrence Wegner, deux jeunes autochtones morts dix ans après Stonechild, et j’explore deux mouvements dans l’espace et le temps : Niastus et Wegner traversant la ville pour trouver la mort dans un champ gelé de la zone nord-ouest, et le cheminement que l’enquête nous invite à faire en nous faisant croire que Niastus et Wegner sont les seuls responsables de leur décès. Dans le panorama des décès d’autochtones en détention en Saskatchewan, y compris en prison, par suicide et à la suite de violents affrontements avec la police, le corps d’un autochtone est un corps qui ne peut être assassiné.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; histoire et politique; hypothermie; justice sociale; meurtre; mort; personnes autochtones; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; violences

Realizing the UN Declaration on the Rights of Indigenous Peoples: triumph, hope, and action - Joffe, Paul; Hartley, Jackie; Preston, Jennifer (Purich Pub., 2010)
Adopted by the UN General Assembly on 13 September 2007, the United Nations Declaration on the Rights of Indigenous Peoples affirms the “minimum standards for the survival, dignity and well-being of the indigenous peoples of the world.” The Declaration responds to past and ongoing injustices suffered by Indigenous peoples worldwide. It provides a strong foundation for improved relationships with states, and for the full recognition of the inherent rights of Indigenous peoples. Despite this, Canada was one of the few countries to oppose the Declaration. The contributors to this collection analyze the development of the Declaration, recall the triumph of its adoption, and illustrate the hopes and actions for its implementation. The discussion moves beyond Canadian borders to the international stage, providing accessible information and guidance on the Declaration and how it can be used to advance human rights. Policy makers, Indigenous communities, politicians, academics, lawyers, human rights advocates, NGOs, and anyone interested in the significance of the Declaration will find this to be a valuable resource. Contributors include Indigenous leaders, legal scholars and practitioners, state representatives, and representatives from NGOs, with extensive knowledge of and experience in Indigenous peoples’ human rights law, policy, and practice.
Keywords: 2000 à aujourd'hui; 2000-2009; ONU; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; droits des personnes autochtones; histoire et politique; justice sociale; pol4105; premier cycle; premiers peuples; premières nations; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences

Le projet de loi C-3 ou le mythe d’une loi non discriminatrice - Masmoudi, Sakina (Recherches amérindiennes au Québec, 2009)
Le projet de loi C-3, déposé à la Chambre des Communes le 11 mars 2010, fait suite à l’arrêt McIvor du 6 avril 2009 de la Cour d’appel de la Colombie-Britannique (CACB). Ce jugement déclare que les dispositions de la Loi sur les Indiens relatives à l’inscription et à la transmission du statut d’Indien contreviennent à l’article 15 de la Charte canadienne des droits et libertés. Plus précisément, le jugement vise l’article 6 de la Loi sur les Indiens auquel des amendements ont été apportés en 1985 par le projet de loi C-31. À l’époque, de nombreuses voix avaient déploré les discriminations résiduelles de ce projet de loi. Vingt-cinq ans plus tard, le Parlement du Canada se penche enfin sur ces discriminations, s’évertuant à apporter des corrections bien tardives et insuffisantes.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; cours; discipline; droit; droits des femmes*; histoire et politique; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; système pénal; systèmes d'oppressions; thématiques